The Equivalence of Video Self‐review Versus Debriefing After Simulation: Can Faculty Resources Be Reallocated? - Tudor, Gregory J. (AEM Educ Train, 2019)
INTRODUCTION: Traditional simulation debriefing is both time‐ and resource‐intensive. Shifting the degree of primary learning responsibility from the faculty to the learner through self‐guided learning has received greater attention as a means of reducing this resource intensity. The aim of the study was to determine if video‐assisted self‐debriefing, as a form of self‐guided learning, would have equivalent learning outcomes compared to standard debriefing. METHODS: This randomized cohort study consisting of 49 PGY‐1 to ‐3 emergency medicine residents compared performance after video self‐assessment utilizing an observer checklist versus standard debriefing for simulated emergency department procedural sedation (EDPS). The primary outcome measure was performance on the second EDPS scenario. RESULTS: Independent‐samples t‐test found that both control (standard debrief) and intervention (video self‐assessment) groups demonstrated significantly increased scores on Scenario 2 (standard—t(40) = 2.20, p < 0.05; video—t(45) = 3.88, p < 0.05). There was a large and significant positive correlation between faculty and resident self‐evaluation (r = 0.70, p < 0.05). There was no significant difference between faculty and residents self‐assessment mean scores (t(24) = 1.90, p = 0.07). CONCLUSIONS: Residents receiving feedback on their performance via video‐assisted self‐debriefing improved their performance in simulated EDPS to the same degree as with standard faculty debriefing. Video‐assisted self‐debriefing is a promising avenue for leveraging the benefits of simulation‐based training with reduced resource requirements.